Microstrip Bandpass Filter with Reconfigurable Notch Response at 5.2 GHz using Defected Microstrip Structure - Mutalib, Mohamad Ariffin; Zakaria, Z.; Shairi, N.A.; Isa, M.S.M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
An investigation of a new design of short circuit stub wideband bandpass filter integrated with reconfigurable notch characteristic is presented. The wideband bandpass filter was designed from a quarter-wavelength short circuit stub with folded topology in order to reduce overall physical dimension. The U-shaped DMS was designed on a microstrip line by defecting the bandpass filter. The reconfigurable characteristic was then realized by introducing PIN diode (BAP 64-02) as a switching element that is placed on top of the U-shaped DMS. When the diode was OFF, it produced a wideband bandpass response from 3.0 GHz to 6.0 GHz. On the other hand, when the PIN diode was ON, a sharp rejection of notch response at 5.2 GHz with a very low passband transmission coefficient was finally demonstrated. This type of filter is very useful in radar and wireless communication systems.